The indigenous people Suku Anak Dalam Batin Sembilan livelihood: Adaptation and socio-cultural dynamics - Indrizal, Edi; Anwar, Hairul (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
The Suku Anak Dalam (SAD) Batin Sembilan living in the Hutan Harapan area of Jambi Province has experienced socio-cultural dynamics resulting from the impacts of development and ecological changes of forest. The various interventions of extractive companies and others (Orang Terang) require them to learn new things that are absent in their knowledge system and traditional way of life. The present study is based on anthropological studies that rely on qualitative methods with a cultural ecology perspective aiming to describe the adaptive actions of SAD Batin Sembilan in responding to changes in their physical and socio-cultural environment as well as the reconstruction of their cognitive. The findings show that although they have long been in contact with people from outside the community, suggesting an influence on the way of thinking, living, and fulfilling their needs or livelihood, the SAD community seems to have preserved their socio-cultural identity closely associated with life dependence on forest. This study sheds new light on the actual picture of the SAD Batin Sembilan community in responding to changes.